2020
DOI: 10.1038/s10038-020-00864-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of an IGHV3-66 gene variant with Kawasaki disease

Abstract: In a meta-analysis of three GWAS for susceptibility to Kawasaki disease (KD) conducted in Japan, Korea, and Taiwan and follow-up studies with a total of 11,265 subjects (3428 cases and 7837 controls), a significantly associated SNV in the immunoglobulin heavy variable gene (IGHV) cluster in 14q33.32 was identified (rs4774175; OR = 1.20, P = 6.0 × 10 −9). Investigation of nonsynonymous SNVs of the IGHV cluster in 9335 Japanese subjects identified the C allele of rs6423677, located in IGHV3-66, as the most signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Significant genome-wide associations were also detected for SNPs in HLA class II genes in the Japanese population ( Onouchi et al, 2012 ), whereas analyses performed with specific HLA class I alleles yielded nonreproducible results ( Onouchi, 2009 ). Finally, a recent follow-up study of the three East Asian GWASs identified several additional significant loci ( Johnson et al, 2020 ; Lee et al, 2012 ; Onouchi et al, 2012 ; Table 2 ). In particular, a higher risk of KD was found to be associated with the high-expression alleles of SNPs located in the Ig heavy variable gene (IGHV) cluster.…”
Section: Human Genetic Studies Of Kd: Gwasmentioning
confidence: 98%
See 1 more Smart Citation
“…Significant genome-wide associations were also detected for SNPs in HLA class II genes in the Japanese population ( Onouchi et al, 2012 ), whereas analyses performed with specific HLA class I alleles yielded nonreproducible results ( Onouchi, 2009 ). Finally, a recent follow-up study of the three East Asian GWASs identified several additional significant loci ( Johnson et al, 2020 ; Lee et al, 2012 ; Onouchi et al, 2012 ; Table 2 ). In particular, a higher risk of KD was found to be associated with the high-expression alleles of SNPs located in the Ig heavy variable gene (IGHV) cluster.…”
Section: Human Genetic Studies Of Kd: Gwasmentioning
confidence: 98%
“… This table lists variants reaching genome-wide significance (P < 5 × 10 −8 ) in the primary GWAS in which they were identified ( Khor et al, 2011 ; Kim et al, 2017 ; Lee et al, 2012 ; Onouchi et al, 2012 ) or in a follow up meta-analysis ( Johnson et al, 2020 ) of the three Asian GWASs ( Kim et al, 2017 ; Lee et al, 2012 ; Onouchi et al, 2012 ). Chr, chromosome; SNP, single nucleotide polymorphism; UTR, untranslated region.…”
Section: Human Genetic Studies Of Kd: Gwasmentioning
confidence: 99%
“…In a simian immunodeficiency virus infection model, the TR alleles response for the potent CD8+ T cell response was recently determined 10 . Germline AIRR alleles have started to be found associated with human diseases, including celiac disease 11 , Alzheimer disease 12 , rheumatic heart disease 13 , and Kawasaki disease 14 ; 15 . However, the known examples of germline AIRR effects on human immune-related phenotypes and diseases are likely only the tip of the iceberg because determining germline AIRR for any given individual is currently insurmountable.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic differences, such as those observed between 129S1/SvImJ and C57BL/6 (Figures 2A, B), when considered alongside observations that have been made for regulatory elements elsewhere in the genome, raise important questions about the potential for Ig genetic diversity to impact V(D)J recombination. First, there are numerous examples for which germline V H variants have been shown to contribute to antigen specificity (75-79) and associate with disease and clinical phenotypes in the context of infection, inflammation, and vaccination (31,32,(80)(81)(82)(83). Second, both large structural variants and single nucleotide polymorphisms could modify key regulatory elements, such as CTCF sites and in promoters and enhancers, either through the disruption of these elements (e.g.…”
Section: Discussionmentioning
confidence: 99%